Advances in renewable energies offshore : proceedings of the 3rd International Conference on Renewable Energies Offshore (RENEW 2018), 8-10 October 2018, Lisbon, Portugal /: proceedings of the 3rd International Conference on Renewable Energies Offshore (RENEW 2018), 8-10 October 2018, Lisbon, Portugal. ([2019]) - Unknown
No abstract available